Mechanism of Action in Burst Spinal Cord Stimulation: Review and Recent Advances. (1st June 2019) - Chakravarthy, Krishnan; Fishman, Michael A; Zuidema, Xander; Hunter, Corey W; Levy, Robert
Abstract: Objective: This is a comprehensive, structured review synthesizing and summarizing the current experimental data and knowledge about the mechanisms of action (MOA) underlying spinal cord stimulation with the burst waveform (as defined by De Ridder) in chronic pain treatment. Methods: Multiple database queries and article back-searches were conducted to identify the relevant literature and experimental findings for results integration and interpretation. Data from recent peer-reviewed conference presentations were also included for completeness and to ensure that the most up-to-date scientific information was incorporated. Both human and animal data were targeted in the search to provide a translational approach in understanding the clinical relevance of the basic science findings. Results/Conclusions: Burst spinal cord stimulation likely provides pain relief via multiple mechanisms at the level of both the spinal cord and the brain. The specific waveforms and temporal patterns of stimulation both play a role in the responses observed. Differential modulation of neurons in the dorsal horn and dorsal column nuclei are the spinal underpinnings of paresthesia-free analgesia. The burst stimulation pattern also produces different patterns of activation within the brain when compared with tonic stimulation. The latter may have implications for not only the somatic components of chronic pain but also the lateral and affective pathway dimensions as well.